The Foguang Buddhist Canon: the unique and creative classification of Buddhist works - Yikung (Studies in Chinese Religions, 2016)
Since 1977, the Compilation Committee of the Foguang Buddhist Canon has endeavored to produce an updated, newly collated Chinese Buddhist canon that is more accessible to both Buddhist practitioners and scholars. This paper firmly grounds the project in the history of canon compilation in East Asia, considers the innovative approach of the modern Foguang Buddhist Canon, and outlines the goals for the canon’s continued growth in the future in five parts: (1) the introduction of Buddhism into China and early scripture translations; (2) the formation of the Chinese Buddhist canon; (3) the various engraved editions of the canon; (4) the newly collated Foguang Buddhist Canon; and (5) future tasks for the Compilation Committee.